The Stories by Kayes Ahmed: An Existentialist Study - Haq, A K M Mahbubul (Jagannath University Journal of Arts, 2026)
Kayes Ahmed [1942-1992] is a relevant and unique writer in Bangladeshi fiction. In particular, the form and content of his stories are experimental and innovative. Kayes Ahmed is one of the few writers in Bangladeshi fiction in the seventies who adopted psychoanalytical narratives as subject and stream-of-consciousness as the form. His stories contain artistic commentary on the fatigue, grief, melancholy, isolation, and meaninglessness of middle-class life. Riots, famine, partition in 1947, the liberation war in 1971 and post-liberation social chaos have also become the subject of his stories. In fact, he embodies the struggle for existence of people in the perspective of the country and history. This article examines the struggle and potential for salvation of helpless people, surrendered and devastated by the state, society, and surroundings depicted in Kayes's story in the light of existentialist philosophy. This extract shows how important the role of their class position and environment is in dealing with existential crises. The present article also analyzes the multifaceted nature of death and the advent of suicide in Kayes' story in view of existentialist philosophy. Kayes Ahmed did not set out to create the 'free man' of existentialist philosophy in his story; he wanted to show people with minimal dignity so that others would be encouraged. One of the objectives of this article is to identify those people with the help of an existentialist reading of Kayes's stories. Jagannath University Journal of Arts, v-15, i-2, 2025:p76-91